INDONESIA DALAM PERKEMBANGAN IPTEK DAN EKONOMI PADA MASA COVID-19 - Agus Rustamana; Clarisa Dwi Hanita; Nurul Rohmah (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
Covid-19 has limited many community activities in Indonesia, which has led to every individual being advised to stay at home. Of course, it has a huge impact on all areas of life, the health sector which is continuously highlighted has an influence on technological developments and the ups and downs of economic conditions in Indonesia. This research focuses on literature study to obtain secondary data obtained online through official government websites, online journals and ebooks. The results of this research are that technological developments are increasingly developing during the Covid-19 era. The limited number of activities requires people to utilize existing technology and trigger the presence of renewable technology. The always fluctuating economic sector made Indonesia slump in the early days of Covid-19, starting from changes in the world supply chain to the decline in foreign investment into Indonesia. This decline can be seen through the slowdown in economic growth, which fell from 5.02 percent in 2019 to 2.97 percent in 2020. The slowdown in economic growth was also accompanied by an increase in the number of unemployed, which according to World Bank data, increased from 5.28 percent. in 2019 it became 7.07 percent in 2020. Covid-19 has provided many breakthroughs so that now in 2023 all areas of life cannot be separated from technology, including the economy in Indonesia which is quite dependent on technological developments.